(untitled) (Sir Salimullah Medical College Journal, 2022)
Background: Physical medicine and rehabilitation (PM&R) is a medical speciality focused on prevention, diagnosis, rehabilitation, and therapy for patients who experience functional limitations resulting from injury, disease, or malformation. Department of Physical Medicine and Rehabilitation (PMR) at Sir Salimullah Medical College and Mitford Hospital provides outdoor services for different musculoskeletal and neurological disorders which include counseling, drug management, physical therapy, speech therapy, ADL training etc. In this study, we enrolled only the patients of musculoskeletal disorders. Objectives: To understand the disease pattern and demographic characteristics of the patients of Musculoskeletal disorders presenting to the department of PMR. This will increase the awareness regarding PMR services among doctors and other health care providers and also to facilitate rehabilitation plan of a musculoskeletal disorder. Methods: This cross-sectional observational study was done on outdoor patients attending the Department of PMR at Sir Salimullah Medical College from 1st January, 2021 to 31st December, 2021. We have enrolled only the patients of musculoskeletal disorders. Results: Total number of patients was 13644, most of them were female. Maximum number of patients belong to 20-50 years of range and they mainly come from surrounding urban areas. Regarding the musculoskeletal disease pattern, 34.2% patients presented with mechanical low back pain (LBP) and related diseases, 11.4% patients with neck pain, 13.7% with knee pain, 9.4% with shoulder pain, soft tissue rheumatism (STR) comprises of 8.7%, 4.6% with heel pain and related disorders, 14.3% with rheumatological diseases, other musculoskeletal diseases contribute to 3.7%. Patients with LBP and related diseases were diagnosed as non-specific mechanical LBP (74%), Herniated disc disease(5%), Lumbar spondylosis, Spondylolisthesis (2%), etc. Conclusion: LBP and related diseases affect most of the people attending outdoor with musculoskeletal diseases. Sir Salimullah Med Coll J 2022; 30: 186-189